Competition in the U.S. Labor Market - Martin Prachowny (Queen's University, Department of Economics, 1994)
Why do unemployed workers resist competing for jobs by offering to work for less than existing workers? Solow has posited a rational social norm that dictates against such behavior. Here the emphasis is on the barrier to competition presented by hiring and training costs that protect existing workers. Empirical evidence is presented for these costs (about 2,500 per year in the late 1980s) by measuring the opportunity cost of overtime hours in U.S. manufacturing industries. This protection also gives currently employed workers an incentive to raise wages - as long as continued employment is secure. They outnumber the unemployed who want lower wages by roughly 10 to 1. If wages are determined "democratically" the former group is able to slow down real wage reductions in recessions and speed up wage increases in booms, resulting in the usually observed asymmetrical movements around the natural rate of unemployment. By using an empirical labor-use curve, it is estimated that in 1987 a reduction of employment by about 1% (about 1.1 million workers) would have given an extra 114 per year to the remaining 111 million workers.
Keywords: 330